Interactive storytelling for the screen - Rene Meyer, Sylke (Perform, 2021)
"An invaluable collection of essays and interviews exploring the business of interactive storytelling, this highly accessible guide offers invaluable insight into an ever-evolving field that is utilising new spatial and interactive narrative forms to tell stories. This includes new media filmmaking and content creation, a huge variety of analog story world design, eXtended realities, game design, and VR design. The book contains essays written by and interviews with working game designers, producers, 360-degree filmmakers, immersive theatre creators and media professors, exploring the business side of interactive storytelling - where art meets business. Contributors to this book will share their perspectives on how to break into the field; how to develop, nurture, and navigate business relationships; expectations in terms of business etiquette; strategies for contending with the emotional highs and lows of interactive storytelling; how to do creative work under pressure; the realities of working with partners in the field of new media narrative design; prepping for prototyping; writing analog and digital; and more. This is an idea resource for students of filmmaking, screenwriting, media studies, RTVF, game design, VR and AR design, theatre, and journalism that are interested in navigating a career pathway in the exciting field of interactive storytelling"--